Women’s voices in civil society organizations: Evidence from a civil society mapping project in Mali - Bleck, Jaimie; Gottlieb, Jessica; Kosec, Katrina; Boss, Lindsey (International Food Policy Research Institute, 2021)
Tremendous optimism prevails around bottomup accountability — a situation in which citizens effectively hold their government to account. This contrasts with top-down accountability, whereby higher tiers of governments, donors, or nongovernmental organizations (NGOs) fulfill this role by restraining, monitoring, and rewarding or sanctioning government. Bottom-up accountability can involve direct citizen participation (often involving efforts to provide them information, voice, and involvement in policymaking) or can be mediated through civil society organizations (CSOs) that monitor and potentially reward or sanction government. A large variety of different types of CSOs exist, distinguished both by their organizational purpose and the composition of their membership, possibly with different willingness and ability to hold government accountable.